Limited war revisited - Osgood, Robert E. (Boulder Westview Press, 1979)
The author examines the succes, ambiguities, and flaws of the strategy in its expanding application to postwar military policy. He interprets its impact on the Vietnam war and vice versa, extends his analysis to the new challanges posed by changes in technology and the military balance that affect U.S. security, and concludes with a searching inquiry into the problems of limited war where its utility as an instrument of foreign policy is now most in doubt: the Third War.
Keywords: Politics